1999
DOI: 10.1136/bmj.319.7211.660a
|View full text |Cite
|
Sign up to set email alerts
|

Storm rages over revisions to Helsinki Declaration

Abstract: A group of UK medical journal editors has issued best practice guidelines to help stem research misconduct, a problem characterised by its chairman as "endemic" in the United Kingdom and the United States. The guidelines, drawn up by the Committee on Publication Ethics (COPE), are intended to promote and safeguard intellectual honesty at all stages in the research and publication cycle, from initial study design onwards. Ethical approval, data analysis, competing interests, authorship, peer review, redundant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Placebos can exist in various forms and can be classified as pharmacological (such as a tablet), physical (for example, a manipulation) or psychological (for example, a conversation) [6]. The ethical debate regarding placebos has continued for several years and concerns about their use remain unresolved [7–10].…”
mentioning
confidence: 99%
“…Placebos can exist in various forms and can be classified as pharmacological (such as a tablet), physical (for example, a manipulation) or psychological (for example, a conversation) [6]. The ethical debate regarding placebos has continued for several years and concerns about their use remain unresolved [7–10].…”
mentioning
confidence: 99%
“…The debate has taken on international political importance because it has been acknowledged that such a study would never be tolerated in the western industrialized countries (McNeill, 1998). Dirceu Greco, professor of internal medicine at the Federal University of Minas Gerais, Brazil, suggested that concerns about exploitation of economically deprived countries by industrialized countries would be avoided if the new drug or treatment were tested in the country in which it is to be marketed (Ramsay, 1999;Woodman, 1999).…”
Section: Current Concepts In Neurotherapy 75mentioning
confidence: 99%
“…This most recent revision in the Declaration (the document was previously revised in 1975, 1983, 1989, and 1996) is aimed at making the document relevant to today's field of medical research. As medicine becomes ever more global in its reach, the controversy regarding local or universal standards of care will continue to challenge both the interests of society and the interests of the individual patients [1][2][3][4][5][6].…”
mentioning
confidence: 99%